Identification of circadian clock modulators from existing drugs. Issue 5 (17th April 2018) - Tamai, T Katherine; Nakane, Yusuke; Ota, Wataru; Kobayashi, Akane; Ishiguro, Masateru; Kadofusa, Naoya; Ikegami, Keisuke; Yagita, Kazuhiro; Shigeyoshi, Yasufumi; Sudo, Masaki; Nishiwaki‐Ohkawa, Taeko; Sato, Ayato; et al.
Abstract: Chronic circadian disruption due to shift work or frequent travel across time zones leads to jet‐lag and an increased risk of diabetes, cardiovascular disease, and cancer. The development of new pharmaceuticals to treat circadian disorders, however, is costly and hugely time‐consuming. We therefore performed a high‐throughput chemical screen of existing drugs for circadian clock modulators in human U2OS cells, with the aim of repurposing known bioactive compounds. Approximately 5% of the drugs screened altered circadian period, including the period‐shortening compound dehydroepiandrosterone (DHEA; also known as prasterone). DHEA is one of the most abundant circulating steroid hormones in humans and is available as a dietary supplement in the USA. Dietary administration of DHEA to mice shortened free‐running circadian period and accelerated re‐entrainment to advanced light–dark (LD) cycles, thereby reducing jet‐lag. Our drug screen also revealed the involvement of tyrosine kinases, ABL1 and ABL2, and the BCR serine/threonine kinase in regulating circadian period. Thus, drug repurposing is a useful approach to identify new circadian clock modulators and potential therapies for circadian disorders. Synopsis: Chronic circadian misalignment has long term consequences on our health and leads to increased risk of developing diabetes, cardiovascular disease and cancer. Using a drug repurposing approach, dehydroepiandrosterone (DHEA) was identified as an important circadian clock modulator. Approximately 5% of the screened drugs altered circadian period. DHEA shortened circadian period in cells and tissues. When fed to mice, DHEA shortened circadian period and significantly reduced jet‐lag. ABL1/2 tyrosine kinases and BCR serine/threonine kinase are involved in regulating circadian period. Drug repurposing is a useful approach to identify new circadian clock modulators. Abstract : Chronic circadian misalignment has long term consequences on our health and leads to increased risk of developing diabetes, cardiovascular disease and cancer. Using a drug repurposing approach, dehydroepiandrosterone (DHEA) was identified as an important circadian clock modulator.